A patent review of immunoproteasome inhibitors. (3rd July 2018) - Ogorevc, Eva; Schiffrer, Eva Shannon; Sosič, Izidor; Gobec, Stanislav
ABSTRACT: Introduction : The ubiquitin–proteasome system is responsible for maintaining protein homeostasis and regulating a variety of cellular processes. The constitutive proteasome is expressed in all cells while the immunoproteasome (IP) is predominantly found in cells of hematopoietic origin. In other cells, the expression of IP can be induced under the influence of cytokines released by T cells during acute immune and stress responses. Inhibitors of IP are of significant interest, because it is expected that selective inhibition of the IP would cause fewer adverse effects. Areas covered : There is a considerable interest on patenting IP-specific inhibitors. Relevant patents and patent applications disclosing IP inhibitors are summarized and divided into two parts according to the chemical characteristics of compounds. We also briefly report on the biochemical methods used in the patents to profile the characteristics of IP inhibitors. Expert opinion : Several selective inhibitors of IP with a promising ability to address autoimmune and inflammatory diseases are being developed. Peptidic compounds are prevalent and the most advanced IP-selective compounds to date, ONX-0914 and KZR-616, are tripeptide epoxyketone-based molecules. However, some patents disclose that IP-selective inhibition is possible with compounds possessing non-peptidic scaffolds indicating countless possibilities to address inhibition of IP in the future.